Det stof som middelalderen er gjort af – Om Game of Thrones-tapetets middelaldermediering - Preisler Skovgaard, Ane (Slagmark - Tidsskrift for idéhistorie, 2019)
The Game of Thrones Tapestry is a hand-woven and hand-embroidered tapestry which depicts key moments from the HBO TV series Game of Thrones in the style of the Bayeux Tapestry. By analysing particular aspects of its imagery and materiality, the article states that the Game of Thrones Tapestry confirms the way that the Middle Ages are also depicted in the TV series as a time of brutality, barbarism and permeable grotesque bodies, or in short, as the contrast to Modernity. With reference to Art historian Hans Belting’s image theory, it is suggested that one way in which the tapestry confirms this idea of the Middle Ages is through the properties of its medium because as a symbolic body it resembles the Grotesque Body by being permeable and transformable. Because of the tapestry’s ability to mediate the conception of the Middle Ages that characterises the fictional world of Game of Thrones in general, the article proposes that the tapestry can be regarded as a very suitable medium for the images of Game of Thrones which may also explain why this tapestry was created.